2016
DOI: 10.3390/ijms17010053
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Dysfunction Following Burn Injury: What We Have Learned from Rat and Mouse Models

Abstract: Abstract:Severe burn profoundly affects organs both proximal and distal to the actual burn site. Cardiovascular dysfunction is a well-documented phenomenon that increases morbidity and mortality following a massive thermal trauma. Beginning immediately post-burn, during the ebb phase, cardiac function is severely depressed. By 48 h post-injury, cardiac function rebounds and the post-burn myocardium becomes tachycardic and hyperinflammatory. While current clinical trials are investigating a variety of drugs tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 149 publications
(124 reference statements)
0
58
0
6
Order By: Relevance
“…Cardiac damage is a well-documented event that increases mortality and morbidity after severe burns [9]. Research in in vivo and in vitro models has demonstrated that poor cardiac contractility starts immediately after thermal injury, continues for approximately 36 h after burn, and resolves by 72 h after burn [9,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardiac damage is a well-documented event that increases mortality and morbidity after severe burns [9]. Research in in vivo and in vitro models has demonstrated that poor cardiac contractility starts immediately after thermal injury, continues for approximately 36 h after burn, and resolves by 72 h after burn [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac damage is a well-documented event that increases mortality and morbidity after severe burns [9]. Research in in vivo and in vitro models has demonstrated that poor cardiac contractility starts immediately after thermal injury, continues for approximately 36 h after burn, and resolves by 72 h after burn [9,31]. In this study, we found burn-induced cardiac mitochondrial damage evidenced by disruption of mitochondrial morphology and mitochondrial superstructures, altered activity of the electron transport chain, and decreased mitochondrial oxygen consumption resulting in ATP deficiency and decreased mitochondrial antioxidant enzyme activity (MnSOD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the evidence-based practices in burn care are from very successful single centers that have perfected the research enterprise with a defined patient population, standard treatment algorithms and a consistent surgical team. 11,12 Such centers have well-established basic science, animal, and translational science labs, 13,14 perform randomized-controlled trials to study treatment interventions, 15 and spearhead multi-centered trials. 16,17 These centers have established research protocols describing the risks, benefits, alternatives, and evidence, and have the staff to provide information and resources for patients and families with questions or concerns.…”
Section: Discussionmentioning
confidence: 99%